The New Urban Gothic
XIV, 253 p. 22 illus., 18 illus. in color.
Keywords: This collection explores global dystopic, grotesque and retold narratives of degeneration, ecological and economic ruin, dystopia, and inequality in contemporary fictions set in the urban space. Divided into three sections—Identities and Histories, Ruin and Residue, and Global Gothic—The New Urban Gothic explores our anxieties and preoccupation with social inequalities, precarity and the peripheral that are found in so many new fictions across various media. Focusing on non-canonical Gothic global cities, this distinctive collection discusses urban centres in England’s Black Country, Moscow, Detroit, Seoul, Hong Kong, Bangkok, Singapore, Dehli, Srinigar, Shanghai and Barcelona as well as cities of the imaginary, the digital and the animated. This book will appeal to anyone interested in the intersections of time, place, space and media in contemporary Gothic Studies. The New Urban Gothic casts reflections and shadows on the age of the Anthropocene.